Direct Democracy and Political Extremism - Nicolas Schreiner; Alois Stutzer (Institute of Labor Economics (IZA), 2025)
We study how citizens' right to directly decide on policies through popular initiatives affects the attractiveness of extreme candidates in representative elections. In our theoretical framework, single prominent policy issues on which individual voters hold extreme views get a large weight in their assessment of candidates, thereby favoring ideologically extreme ones. If citizens can decide the controversial policy issues separately on the ballot, this decouples the issues from legislative politics and moderate candidates become relatively more attractive to voters. We apply our theory to U.S. state legislative elections and find that ideologically extreme candidates receive significantly lower voter support in initiative than in non-initiative states. This holds in particular for states with low qualification requirements for initiatives. In concurrent elections for the U.S. House we do not observe this difference in the electoral success of extreme candidates between initiative and non-initiative states. The effect seems partly mediated by lower campaign donations to extreme candidates.
Keywords: D02; D72; 330; campaign donations; direct democracy; extremist ideology; initiative right; moderating selection effect; polarization; political institutions; voting